Compatibility and Stability of Cipepofol (Ciprofol) and Etomidate Mixture for Intravenous Anesthesia - Linzhong Zhang, MD; Lingchun Kong, MA; Qi Deng, MS; Yukai Chao, MA; Chibing Fu, MA; Yutong Meng, MA (Current Therapeutic Research, 2025)
ABSTRACTS: Objective: To evaluate the physical and chemical compatibility and stability of a cipepofol (ciprofol) and etomidate (EC) mixture for intravenous anesthesia and assess the physiochemical stability of the drugs during co-administration through the same intravenous line. Methods: High-performance liquid chromatography and other analytical techniques were employed to investigate the stability of the EC mixture. The mixture was prepared and stored at 4°C, 25°C, or 37°C for 24 h, and its appearance, pH, osmotic pressure, particle size, zeta potential, drug content, and related substances were evaluated at 0, 1, 3, 6, 12, and 24 h. Results: The EC mixture maintained physical stability, with no significant changes in appearance, pH (fluctuation, ≤0.07 units), osmotic pressure (relative standard deviation [RSD] < 2.0%), or particle size observed over 24 h. Zeta potential remained within acceptable limits (ranging from −40 to −30 mV), indicating good colloidal stability. Chemically, drug content remained at ≥99.9% of the initial level (RSD < 1.2%), and impurity levels stayed within the specified limits (maximum single impurity ≤ 0.13%, total impurities ≤ 0.37%). Conclusions: The findings suggest that the EC mixture was physically and chemically compatible and stable for up to 24 h at various temperatures, making this regimen a potentially safe and effective option for intravenous anesthesia. This finding is significant for improving patient comfort and reducing adverse drug reactions during anesthesia induction and maintenance.